General Considerations Regarding the Scientific Research - STĂNCIULESCU, Daniela; STĂNCIULESCU, Sorin (Journal of Research in Educational Sciences; Vol 8 No 10 (2017): Volume VIII, Issue 10, 2017, 2018)
Scientific research is firstly a rational process that allows us to examine the phenomena or issues that we have to resolve and obtain precise answers stating from investigations. This process can be defined as systematic, rigorous and it leads to the acquisition of new knowledge. We may define scientific research as a systematic process through which observable and verifiable data is gathered starting from empiric models. Research is an important source of orientations offered towards the resolution of different business, governmental and social issues.